Cert Prep: SOLIDWORKS Sheet Metal. - Corbett, Gabriel (linkedin.com, 2017)
Prepare for the Certified SOLIDWORKS Professional Advanced Sheet Metal (CSWPA-SM) exam. Refresh your skills with flanges, hems, bend tables, and equations.